INTERPRETATION APPROACH IN THE DYNAMICS OF SHARIA BANKING - Zamakhsyari Abdul Majid (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
Indonesia is a country with the largest Muslim population in the world with a Muslim population of around 204 million. This large Muslim population represents a great potential for the development of Islamic banking. This Islamic banking began to get the government's attention with the issuance of a law that supports Islamic banking. With various policies and decisions from a period of approximately 36 years (1974-2008), starting with the holding of a national seminar on relations between Indonesia and the Middle East which contained the idea of ​​realizing the Islamic Banking Law. This article is a qualitative study. The existence of Islamic-based Rural Banks encourages the establishment of interest-free commercial banks. With various developments that continue to be carried out by the Indonesian Banking, in 2008 the enactment of Law no. 21 of 2008 concerning Islamic Banking which is expected to provide significant prospects for Islamic Banking. Basically the concept in Islam cannot be separated from the 5 pillars of primary needs (al-dlaruriyyatul al-khams), namely: hifdhun nafs (guaranteed protection of the soul), hifdhul 'aql (guaranteed protection of reason), hifdhul mâl (guarantee of property protection), hifdhun nasl (guaranteed protection of offspring), and hifdhud dn (guaranteed protection of religion). Indonesia merupakan negara dengan populasi Muslim terbesar di dunia dengan jumlah penduduk muslimnya sekitar 204 juta jiwa. Populasi Muslim yang besar ini merupakan potensi besar bagi perkembangan perbankan syariah. Perbankan syariah ini mulai mendapat perhatian pemerintah dengan dikeluarkannya undang-undang yang mendukung perbankan syariah. Artikel ini merupakan studi kualitatif. Dengan berbagai kebijakan dan keputusan dari kurun waktu kuranglebih selama 36 tahun (1974-2008), dimulai dari diselenggarakannya seminar nasional hubungan antara Indonesia-Timur Tengah yang berisikan tentang ide merealisasikan UU Perbankan Islam. Keberadaan Bank-bank Perkreditan Rakyat yang berbasis Islam tersebut mendorong untuk didirikannya bank umum yang bebas bunga. Dengan berbagai perkembangan yang terus di lakukan oleh Perbankan Indonesia, pada tahun 2008 disahkannya UU No. 21 Tahun 2008 tentang Perbankan Islam yang diharapkan memberikan prospek yang signifikan bagi Perbankan Islam. Pada dasarnya konsep dalam Islam itu tidak lepas dari 5 pilar kebutuhan primer (al-dlaruriyyatul al-khams), yaitu: hifdhun nafs (jaminan perlindungan jiwa), hifdhul ‘aql (jaminan perlindungan akal), hifdhul mâl (jaminan perlindungan harta), hifdhun nasl (jaminan perlindungan keturunan), dan hifdhud dîn (jaminan perlindungan agama).